IMPLEMENTASI MODEL SUSAN LOUCKS-HORSLEY TERHADAP COMMUNICATION AND COLLABORATION PESERTA DIDIK SMP - Muiz, Abdul; Wilujeng, Insih; Jumadi, Jumadi; Senam, Senam (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2016)
Abstrak ___________________________________________________________________ Seiring perkembangan zaman, kebutuhan dan tuntutan masyarakat akan terus mengalami perubahan. Faktor globalisasi, perkembangan teknologi, pertumbuhan ekonomi, kompetisi internasional, masalah lingkungan dan perubahan politik merupakan beberapa faktor yang menyebabkan pentingnya mengembangkan kemampuan dan pengetahuan untuk sukses di abad ke XXI. Dalam pendidikan, peserta didik perlu dibekali pengetahuan dan keterampilan yang diperlukan agar dapat berkompetisi dalam menghadapi abad XXI. Peserta didik harus dibekali dengan kompetensi foundational knowledge (to know), humanistic knowledge (to value) dan metaknowledge (to act). Salah satu aspek yang penting dikembangkan yaitu communication and collaboration. Aspek ini merupakan bagian dari kompetensi metaknowledge. Kajian ini bertujuan untuk memberikan gambaran terkait implementasi pembelajaran IPA melalui penerapan model Susan Loucks-Horsley untuk meningkatkan communication and collaboration peserta didik. Dalam artikel ini akan dikaji beberapa hal diantaranya pembelajaran IPA, Model Susan Loucks-Horsley serta keterampilan abad XXI yaitu communication and collaboration. Setelah memahami uraian mengenai pembelajaran IPA berbasis model Susan Loucks-Horsley diharapkan guru dan calon guru IPA memiliki ide baru dan tambahan wawasan dalam mengimplementasikan pembelajaran IPA. Abstract ___________________________________________________________________ Along with the times, the needs and demands of society will continue to change. Factors of globalization, technological development, economic growth, international competition, environmental issues and political changes are some of the factors that led to the importance of developing the skills and knowledge to succeed in the XXI century. In education, students need to be equipped with knowledge and skills necessary to compete in the face of the XXI century. Learners must be equipped with the competence foundational knowledge (to know), humanistic knowledge (to value) and metaknowledge (to act). One important aspect is communication and collaboration developed. This aspect is part of competence metaknowledge. This study aims to provide an overview regarding the implementation of learning science through the application of models Susan Loucks-Horsley to improve communication and collaboration of learners. In this article will be reviewed several things including learning science, Model Susan Loucks-Horsley and XXI century skills ie communication and collaboration. After understanding the description of the model-based science learning Susan Loucks-Horsley expected of teachers and prospective science teachers have new ideas and additional insights in implementing learning science. Â Â